2016
DOI: 10.1371/journal.pone.0152963
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Ecological and Morphological Distinctness of the Blue Mussels Mytilus trossulus Gould and M. edulis L. in the White Sea

Abstract: Two blue mussel lineages of Pliocene origin, Mytilus edulis (ME) and M. trossulus (MT), co-occur and hybridize in several regions on the shores of the North Atlantic. The two species were distinguished from each other by molecular methods in the 1980s, and a large amount of comparative data on them has been accumulated since that time. However, while ME and MT are now routinely distinguished by various genetic markers, they tend to be overlooked in ecological studies since morphological characters for taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 72 publications
2
47
1
Order By: Relevance
“…In the present study, the sample WS1 that contained M. trossulus and their hybrids were collected directly in the area of the White Sea Biological Station Kartesh, which has a regular ship connection with Chupa, a small town in Kandalaksha Bay. Recently, M. trossulus was found in the Chupa harbor (Katolikova, Khaitov, Vänölä, Gantsevich, & Strelkov, ), where ship traffic from the Barents Sea has been relatively intensive. In contrast, the WS2 site with pure M. edulis in the sample is located on an uninhabited island Kondostrov in the Onega Bay, which is far from the towns with intensive ship traffic.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the sample WS1 that contained M. trossulus and their hybrids were collected directly in the area of the White Sea Biological Station Kartesh, which has a regular ship connection with Chupa, a small town in Kandalaksha Bay. Recently, M. trossulus was found in the Chupa harbor (Katolikova, Khaitov, Vänölä, Gantsevich, & Strelkov, ), where ship traffic from the Barents Sea has been relatively intensive. In contrast, the WS2 site with pure M. edulis in the sample is located on an uninhabited island Kondostrov in the Onega Bay, which is far from the towns with intensive ship traffic.…”
Section: Discussionmentioning
confidence: 99%
“…From our data, as well as from the literature [17,20,48], it is shown that while M. edulis is distributed mostly discontinuously along the coasts of Europe up to the very distribution border in the Pechora Sea (69.5 • N, [18,20]), the distribution of M. trossulus is sparse with one large population in the inner Baltic Sea and small outposts in Loch Etive in Northern Scotland (LET), the Bergen area in Western Norway (BER), and harbor areas in the White (CHU) and Barents (KOL) Seas in Russia. Several more M. trossulus outposts in the White and Barents Seas, all from harbor areas, were also reported [20,94]. Single locus-based data indicated that M. trossulus could be more widespread in Western Norway [95] and in North-western Scotland [96].…”
Section: Distribution Of Mytilus Taxa On the Coasts Of North Atlanticmentioning
confidence: 99%
“…trossulus into the Atlantic 59 – 61 . Nowadays this species is widespread in the North Atlantic from the Gulf of Maine to the Arctic along the North American coast, and within the Baltic Sea 62 , as well as along the North West Pacific from the East Bering Sea to California, and is an invader in other regions 38 . For its wide distribution it might be taken as a cryptogenic; however, its native distribution is well known and widely reported, and does not include Bay of Biscay, thus we did consider it a NIS.…”
Section: Discussionmentioning
confidence: 99%